Pengaruh Instructional Leadership Kepala Sekolah dan Profesionalisme Guru terhadap Mutu Pembelajaran - Tutianah Tutianah; Nur Ahyani; Mulyadi Mulyadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The purpose of this study is to determine and describe the influence of Instructional Leadership of school principals and teacher professionalism together on the quality of learning of public junior high schools in West Merapi District. held at SMP Negeri se Kecamatan Merapi Barat which consists of 2 (two) schools including: SMP Negeri 1 Merapi Barat and SMP Negeri 2 Merapi Barat. The research method used in this study is quantitative descriptive method. The population and sample in this study amounted to 70 teachers. Data collection techniques using questionnaires, questionnaires and documentation. Data analysis techniques use normality tests, linearity tests, multicollinearity tests, simple correlation analysis, multiple correlation analysis, simple regression analysis, t tests and F tests. The result of this study is that there is a significant influence together between the principal's instructional leadership and teacher professionalism on the quality of learning in West Merapi District. Conclusion: There is a significant joint influence between the principal's instructional leadership and teacher professionalism on the learning quality of State Middle Schools in West Merapi District. Keywords: Instructional Leadership; Professionalism of Teachers; Learning Quality